Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/chem.202203768
|View full text |Cite
|
Sign up to set email alerts
|

RGD Cyclopeptide Equipped with a Lysine‐Engaging Salicylaldehyde Showing Enhanced Integrin Affinity and Cell Detachment Potency

Abstract: Salicylaldehyde (SA) derivatives are emerging as useful fragments to obtain reversible-covalent inhibitors interacting with the lysine residues of the target protein. Here the SA installation at the C terminus of an integrin-binding cyclopeptide, leading to enhanced ligand affinity for the receptor as well as stronger biological activity in cultured glioblastoma cells is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 45 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…As in our earlier work, [15,16] we selected dihydroxybenzaldehyde derivatives (i. e., 2,5-and 2,4-dihydroxybenzaldehydes: Figure 1D, compounds 1 a and 1 b, respectively), with the aim to exploit a second phenolic OH group in the aromatic ring (5-OH or 4-OH) as anchoring unit for the SA installation in the AA side chain. In particular, as illustrated by the retrosynthetic pathway in Scheme 1A, we planned the SA tag connection to the AA scaffold through a Williamson ether synthesis, using the phenolic OH as nucleophile and a leaving group on the AA side chain.…”
Section: Resultsmentioning
confidence: 99%
“…As in our earlier work, [15,16] we selected dihydroxybenzaldehyde derivatives (i. e., 2,5-and 2,4-dihydroxybenzaldehydes: Figure 1D, compounds 1 a and 1 b, respectively), with the aim to exploit a second phenolic OH group in the aromatic ring (5-OH or 4-OH) as anchoring unit for the SA installation in the AA side chain. In particular, as illustrated by the retrosynthetic pathway in Scheme 1A, we planned the SA tag connection to the AA scaffold through a Williamson ether synthesis, using the phenolic OH as nucleophile and a leaving group on the AA side chain.…”
Section: Resultsmentioning
confidence: 99%
“…[41] Our group has recently explored the tailored SA installation into peptide ligands, particularly at the N or C termini of a model cyclic peptide, bearing the ArgÀ GlyÀ Asp (RGD) as wellknown recognition sequence for integrin α V β 3 . [42] The latter features four solvent-exposed Lys near the peptide binding site, which lies at the interface of the protein subunits. Competitive binding assays indicated that the naive ligand strongly inhibits the binding of vitronectin (i. e., a natural integrin ligand bearing the RGD motif) to the receptor (IC 50 � 6 nM).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high frequency of Lys in proteins and the preferential expression of this amino acid on external protein layers, it can be foreseen that SAbearing compounds will be extensively applied in the future to hit undruggable targets and key protein-protein interactions. [42] The covalent docking figures were originally edited with Schrödinger Maestro graphical interface (Schrödinger Release 2021-1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations